Odd Thomas [videorecording (DVD)] - Sommers, Stephen; Yelchin, Anton; Timlin, Addison, 1991-; Dafoe, Willem; Koontz, Dean R. (Dean Ray), 1945- (RLJ Entertainment, 2014)
Small-town fry cook Odd Thomas is an ordinary guy with a paranormal secret: he sees dead people, everywhere. When a creepy stranger shows up with an entourage of ghostly "bodachs"- predators who feed on pain and portend mass destruction- Odd knows that his town is in serious trouble. Teaming up with his sweetheart, Stormy, and the local sheriff, Odd will plunge into an epic battle of good vs evil to try and stop a disaster of apocalyptic proportions.